"This is a question we have to ask everyone": asking young people about self‐harm and suicide. Issue 8 (8th August 2016) - O'Reilly, M.; Kiyimba, N.; Karim, K.
Accessible summary: What is known on the subject?: An essential part of the mental health assessment is to evaluate the risk of harm to self. Fundamentally this involves asking directly about self‐harming behaviour and suicidal thoughts or urges, but practitioners often find it difficult to open up these conversations. This evaluation of risk is particularly important as self‐harm and suicidal thoughts are frequently found in young people who attend mental health services. What this paper adds to existing knowledge?: Young people are not always routinely asked directly about self‐harm or suicidal thoughts when they are assessed. There are two ways that mental health practitioners introduce this topic: first, by building up to it by initially asking about general feelings, and second by stating that it is a requirement to ask everyone. What are the implications for practice?: These questions should not be avoided by mental health practitioners just because they are difficult. We offer suggestions as to how to ask questions about self‐harm and suicide based on real‐world practice. Abstract: Introduction: Questions about self‐harm and suicide are essential in risk assessments with children and young people, yet little is known about how mental health practitioners do this. Aim: The core aim was to examine how questions about self‐harm and suicidal ideation are asked in real‐world practice. Method: A qualitative design was employed to analyse 28 video‐recorded naturally occurring mental health assessments in a child and adolescent mental health service. Data were analysed using conversation analysis (CA). Results: In 13 cases young people were asked about self‐harm and suicide, but 15 were not. Analysis revealed how practitioners asked these questions. Two main styles were revealed. First was an incremental approach, beginning with inquiries about emotions and behaviours, building to asking about self‐harm and suicidal intent. Second was to externalize the question as being required by outside agencies. Discussion: The study concluded that the design of risk questions to young people had implications for how open they were to engaging with the practitioner. Implications for practice: The study has implications for training and practice for psychiatric nurses and other mental health practitioners in feeling more confident in communicating with young people about self‐harm and suicidal ideation.